PENGEMBANGAN MEDIA BONEKA JARI UNTUK MEREDUKSI PERILAKU AGRESIF DAN MENINGKATKAN PERKEMBANGAN MORAL ANAK - Annisa Pujia Astuti; Sri Ulfayati; Ida Ermiana (STKIP Subang, 2026)
Moral and religious development in early childhood is a fundamental phase that is highly susceptible to environmental influences. This research was motivated by the discovery of verbal aggression in the form of abusive language among early childhood students at State Kindergarten 12, East Praya. This study used Research and Development (R&D) methods to develop finger puppets as an intervention tool to reduce verbally aggressive behavior while enhancing children's moral development. The results showed that the root causes of abusive language were influenced by overly indulgent parenting, being the youngest child, and imitation of interactions with older children. The impact of this behavior disrupted social relationships, triggered imitation, and created a negative environmental climate. Responsive actions from teachers through humane reprimands, advice, reinforcement of classroom rules, and collaboration with parents proved crucial. The innovative use of finger puppets with three contrasting emotional expressions within a single character, along with role-playing methods, can facilitate children's emotional recognition, internalization of politeness values, and positive socio-emotional regulation of their behavior.